2007
DOI: 10.1523/jneurosci.4800-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Learning Decreases Aβ*56 and Tau Pathology and Ameliorates Behavioral Decline in 3xTg-AD Mice

Abstract: Transgenic mouse models of Alzheimer's disease (AD), such as the 3xTg-AD mice, are instrumental for elucidating genetic, pharmacologic, environmental, and behavioral factors that affect the cognitive phenotype. Here we present the novel findings that longitudinal water-maze spatial training produces a significant, albeit transient, improvement in subsequent learning performance and reduces amyloid ␤ (A␤) and tau neuropathology. The 3xTg-AD mice were trained and tested at 3 month intervals from 2 to 18 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 50 publications
6
105
4
2
Order By: Relevance
“…Similarly, Ab*56 has been associated with memory deficits in the 3xTg-AD mouse (which harbour the Swedish APP, P301L-t and PS1 M146V mutations), independent of Ab plaque formation. 36 The researchers observed that spatial training resulted in delayed Ab plaque deposition, reduced t-aggregation and reduction in Ab*56 levels. This training effect was most pronounced in young and middle-aged mice, as no effect was observed in aged animals, lending further support to the notion that the younger brain is more capable of handling AD-like lesions than the aged brain.…”
Section: Biology Of Ab In the Brain And Peripherymentioning
confidence: 99%
“…Similarly, Ab*56 has been associated with memory deficits in the 3xTg-AD mouse (which harbour the Swedish APP, P301L-t and PS1 M146V mutations), independent of Ab plaque formation. 36 The researchers observed that spatial training resulted in delayed Ab plaque deposition, reduced t-aggregation and reduction in Ab*56 levels. This training effect was most pronounced in young and middle-aged mice, as no effect was observed in aged animals, lending further support to the notion that the younger brain is more capable of handling AD-like lesions than the aged brain.…”
Section: Biology Of Ab In the Brain And Peripherymentioning
confidence: 99%
“…It is unclear how continuous P4 affects GSK-3␤, although our data predict that extended P4 exposure alters the balance of taurelevant kinase and phosphatase activities to yield a net decrease in pathological tau phosphorylation. Interestingly, previous studies have demonstrated that GSK-3␤-dependent regulation of tau hyperphosphorylation is related to behavioral performance in 3xTg-AD mice (Billings et al, 2007), which suggests a potentially important connection between the effects of progesterone on tau hyperphosphorylation and cognition in AD patients.…”
Section: Discussionmentioning
confidence: 97%
“…Behavioral studies have indicated further important components of the phenotype in separate lines of PDAPP mice including both age-related and age-independent deficits in spatial learning (Chen et al 2000;Dodart et al 2000). These and other important lines of transgenic mice carrying human mutations that occur in familial Alzheimer's disease show learning deficits in a variety of other cognitive tasks (Hsiao et al 1996;Chapman et al 1999;Kobayashi and Chen 2005;Billings et al 2007;Eriksen and Janus 2007).…”
mentioning
confidence: 99%